Cervical cancer diagnosis and treatment delays in the developing world: Evidence from a hospital-based study in Zambia - Jane Mwamba Mumba; Lackson Kasonka; Okola Basil Owiti; John Andrew; Mwansa Ketty Lubeya; Lufunda Lukama; Charlotte Kasempa; Susan C. Msadabwe; Chester Kalinda (Elsevier, 2021)
Expedited diagnostic processes for all suspected cervical cancer cases remain essential in the effort to improve clinical outcomes of the disease. However, in some developing countries like Zambia, there is paucity of data that assesses factors influencing diagnostic and treatment turnaround time (TAT) and other metrics vital for quality cancer care. We conducted a retrospective hospital-based study at the Cancer Diseases Hospital (CDH) for cervical cancer cases presenting to the facility between January 2014 and December 2018. Descriptive statistics were used to summarize demographic characteristics while a generalized linear model of the negative binomial was used to assess determinants of overall TAT. Our study included 2121 patient case files. The median age was 49 years (IQR: ±17) and most patients (n = 634, 31%) were aged between 41 and 50 years. The International Federation of Gynaecology and Obstetrics (FIGO) Cancer stage II (n = 941, 48%) was the most prevalent while stage IV (n = 103, 5.2%) was the least. The average diagnostic TAT in public laboratories was 1.48 (95%CI: 1.21-1.81) times longer than in private laboratories. Furthermore, referral delay was 55 days (IQR: 24-152) and the overall TAT (oTAT) was 110 days (IQR: 62-204). The age of the patient, HIV status, stage of cancer and histological subtype did not influence oTAT while marital status influenced oTAT. The observed longer oTAT may increase irreversible adverse health outcomes among cervical cancer patients. There is a need to improve cancer care in Zambia through improved health expenditure especially in public health facilities.